(3JfbjM GdefGXQ dPhi GdCHUGQ hGdHUGFQs - (3ceGd GdOjf CHi GdMSf GdaGQSis; (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s ((3fjSGHhQ s)
(3ChdgG (B:s
(3GdMeO ddg efhQ GdCfhGQ heXgQ YLGFH GdCSQGQ s
(3gPHg hfbMg HQSe GdEeGe bWH GdOjf CHj GdKfGA eMehO Hf eSYhO GdTjQGRi GdeJhai SfI (B710s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3JgPjHs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs